Naturally occurring anticancer drugs - Danta C.C.; Sahu A.N. (My University, 2025)
Historically, natural products (NPs) have played an essential role in the drug discovery processes, especially for anticancer drug discovery. Researchers have special attraction to NPs in comparison with conventional synthetic molecules as they confer several broad advantages and pose challenges for the new anticancer drug discovery compared with the conventional synthetic molecules. NPs are composed of enormous scaffold diversities and structural complexities, typically possessing a larger number of sp3 carbon and oxygen atoms with less nitrogen and halogen atoms, higher numbers of H-bond acceptors and donors, and lower LogP values. Hence, NPs possess a higher molecular mass and greater molecular rigidity compared with synthetic compounds. © 2023 Elsevier Inc. All rights reserved.